New Keynesian Phillips Curve Estimation: The Case of Hungary (1981–2006) - Aleksandar Vasilev (Managing Global Transitions, 2015)
This paper investigates for the presence of a New Keynesian Phillips (NKPC) curve in Hungary in the period 1981:3–2006:2. The empirical model we test features forward-looking firms who pre-set prices for a couple of periods ahead, using Calvo (1983) pricing rule.We also estimate a hybrid version of NKPC, where some of the firms are backward looking, and others are forward-looking in their price-setting behaviour. Real marginal costs and forward-looking behaviour are statistically significant and quantitatively important in the nkpc.However, there are some econometric issues to be considered, such as the weak identification of the parameters of the structural NKPC as well as those of the hybrid NKPC.
Keywords: C22; E24; 330; New Keynesian Phillips curve; Hungary; instrumental non-linear gmm Estimation; weak identification